2016
DOI: 10.1159/000453264
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Prophylactic and Therapeutic Effects of Polylysine-Modified Ara h 2 DNA Vaccine in a Mouse Model of Peanut Allergy

Abstract: Background: The prevalence of food allergy has been increasing, but treatment is very limited. DNA vaccination has been recognized as a promising method for the treatment of allergic diseases; however, poor immunogenicity has hindered its application. Methods: BALB/c mice were intradermally injected with plasmid DNA encoding the peanut protein Ara h 2 (pAra h 2) or pAra h 2 pretreated with poly-L- lysine (PLL) before or after sensitization with Ara h 2 protein. Ara h 2-specific antibodies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Plasmid DNA encoding the peanut-protein (p) Ara h 2 or pAra h 2 mixed with poly- l -lysine were injected intradermally either before or after sensitization with Ara h 2 [57]. The treatment containing poly- l -lysine was more effective in preventing specific serum antibodies and temperature drop upon challenge when applied before sensitization, inducing CD207 + DCs in draining lymph nodes of skin, CD25 + Foxp3 + Treg cells in lymph nodes and spleen, as well as IFN-γ and IL-10 in splenocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid DNA encoding the peanut-protein (p) Ara h 2 or pAra h 2 mixed with poly- l -lysine were injected intradermally either before or after sensitization with Ara h 2 [57]. The treatment containing poly- l -lysine was more effective in preventing specific serum antibodies and temperature drop upon challenge when applied before sensitization, inducing CD207 + DCs in draining lymph nodes of skin, CD25 + Foxp3 + Treg cells in lymph nodes and spleen, as well as IFN-γ and IL-10 in splenocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, other adjuvants were not tested. For example poly-L-lysine (PLL), which has been reported to improve the prophylactic and therapeutic effect of the peanut allergen Ara h 2 DNA vaccine in peanut-allergic mice [26]. Furthermore, whether the For t 2 DNA vaccine can last long enough to cover the whole midge season requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A high increased secretion of Th2 cytokines (IL-4, IL-5, IL-13) has been observed in all the studies, whereas some discrepancies were observed between allergenic proteins in their potency to induce IFN-γ (Stojadinovic et al, 2014;Vonk et al, 2017) and IL-10 (Vonk et al, 2017). A few studies have measured increased levels of IL-17 (Lozano-Ojalvo et al, 2017;Rupa, Nakamura, Katayama, & Mine, 2014), while in other limited number of studies IL-22 and TNF-α levels showed no differences compared to non-sensitized control cells (Pablos-Tanarro et al, 2016;Zhu et al, 2016).…”
Section: In Vitro Models To Assess Murine Th2 Cell Priming (Ke4)mentioning
confidence: 99%
“…Levels of secreted cytokines are often evaluated by ELISA or flow cytometry in cell culture supernatants. This method has been used to evaluate several food allergens from cow's milk (Kanjarawi et al, 2011;Stojadinovic et al, 2014), peanut (Smit et al, 2015;Zhu et al, 2016), hen's egg (Pablos-Tanarro, Lopez-Exposito, Lozano-Ojalvo, Lopez-Fandino, & Molina, 2016;Sun et al, 2016), soybeans (Sun et al, 2013) and shrimp (Wai et al, 2016). Moreover, extracts from whey, hen's egg white, peanut, cashew, walnut and sesame seeds have also been evaluated using this method (Lozano-Ojalvo et al, 2017;Smit et al, 2015;Vonk et al, 2017).…”
Section: In Vitro Models To Assess Murine Th2 Cell Priming (Ke4)mentioning
confidence: 99%